Analisis Prediksi Erosi dan Erosi yang dapat Ditoleransikan di DAS Kampili Sulawesi Selatan - Hasdi Buranda; Abdul Haris; Amir Tjoneng; Suriyanti Haji Salama; Maimuna Nontji (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2022)
This research was conducted in Kampili Watershed, South Sulawesi. This research was conducted from February to April 2021. This study was conducted using USLE method and USLE formula as an analysis tool to determine the rate of erosion and tolerable erosion as well as identification of damaged land in the Kampili watershed of south Sulawesi. The results showed the rate of erosion that occurs in each land use, namely, in plantation land use has an erosion rate of 94.54-ton ha-1 per year, in the use of mixed plantation land medium density has an erosion rate of 281.10-ton ha-1 per year, in the use of rice fields has an erosion rate of 4.13-ton ha-1 per year and in the use of open land has an erosion rate of 853.53-ton ha-1 per year. The value of erosion that can be tolerated (T) of each land use is, in the use of farmland has a value of T of 17.66-ton ha-1 per year, in the use of mixed garden land density has a value of T of 15.99-ton ha-1 per year, in the use of rice fields has a value of T of 16.40, in the use of open land has a value of T of 12.25-ton ha-1 per year. Meanwhile, for the identification of damaged lands is determined by looking at the value of erosion class that is light, very light, medium, heavy and very heavy.